Effects of various morphologies on the optical and electrical properties of boehmite nanostructures. Issue 40 (26th September 2018) - Roy, Shubham; Maity, Anupam; Mandal, Paulami; Chanda, Dipak Kr.; Pal, Kunal; Bardhan, Souravi; Das, Sukhen
Abstract : This work reports the variations in the fluorescence and ultra-high dielectric properties of various boehmite nano-structures. Abstract : The present article reports three different grain morphologies of boehmite nanoparticles: spherical (EBH), needle-shaped (UBH) and flower-like (HBH). EBH possesses the highest surface area, whereas HBH has the lowest. A novel synthesis route for spherical (EBH) boehmite nanostructures using ethylenediamine has been reported here. Moreover, we have compared the growth mechanisms and morphology-dependent changes in the optical and electrical properties of the three samples. The band gap energies were evaluated to be 5.30 eV, 5.44 and 5.87 eV for EBH, UBH and HBH, respectively. Strong photoluminescence (PL) emission for all the nanostructures, the highest for HBH, was noted. The lowest surface area of HBH provides a surface with fewer defects; this seals the possibility of energy loss via non-radiative recombination of electrons and holes, which enhances the PL intensity. The dielectric constants for EBH, UBH and HBH are 1.49 × 10 6, 1.14 × 10 5, and 7.14 × 10 4, respectively. Variations in the dielectric loss tangents and temperature-dependent electrical properties of the three morphologies were evaluated in support. Also, the ac conductivity and impedance analyses are in good accordance with our dielectric analysis. The present investigation may be highly beneficial in developing biosensors, bio-imaging, and fabricating cost-effective energy storage devices.